America's Original Immunization Controversy: The Tercentenary of the Boston Smallpox Epidemic of 1721. Issue 10 (October 2022) - Nakayama, Don K.
The CoVID-19 pandemic marks the 300th anniversary of the Boston smallpox epidemic of 1721, America's first immunization controversy. Puritan minister Cotton Mather learned of inoculation for smallpox from Onesimus, a man enslaved to him. When the disease broke out in May 1721, Mather urged Boston's physicians to inoculate all those vulnerable to the disease. Zabdiel Boylston, alone among his colleagues, decided to proceed with the procedure, igniting a heated debate that occasionally grew violent. The division between the advocates and detractors of inoculation were as deep as religion and politics. Puritan ministers supported inoculation, asserting their right to control the lives of their flock. Challenging them were a secular class of medical professionals that proclaimed primacy in medical matters. The controversy was inflamed by a nascent newspaper industry eager to profit from the fear of contagion and the passionate debate. Despite the furor and physical risk to himself and his family Boylston inoculated 282 persons, of whom only 6 died (2.1%). Of the 5759 townspeople who contracted smallpox during the epidemic, there were 844 deaths (14.7%). In America's first effort at preventive medicine Boylston established the efficacy of inoculation, which helped support its acceptance in England, and later in the century, the adoption of Edward Jenner's technique of vaccination in 1796.